L’arcipelago postmoderno. Oreste del Buono e gli anni Settanta (ENTHYMEMA, 2012)
Within Italian literary history of the second half of the Twentieth century, Oreste del Buono suffered from a peculiar phenomenon of repression. His involvement in a variety of fields -including genre fiction, comics, literary criticism- makes it difficult to label an eclectic intellectual, quite peculiar if compared to the Italian tradition. However, it is exactly this eclecticism to make Del Buono an original thinker and, at the same time, to make it play the role of mediator within the coeval cultural context. He had in fact embodied the role of mediator between codes and languages, movements and cultural trends, the goals of artistic market and a constant search for quality.  In this paper the figure of Del Buono will be taken as a lens to look at the 1970s from an unusual perspective, this way filling a series of blanks that still inhabit national cultural memory.